2017
DOI: 10.1186/s40793-017-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Leuconostoc suionicum DSM 20241T provides insights into its functional and metabolic features

Abstract: The genome of Leuconostoc suionicum DSM 20241T (=ATCC 9135T = LMG 8159T = NCIMB 6992T) was completely sequenced and its fermentative metabolic pathways were reconstructed to investigate the fermentative properties and metabolites of strain DSM 20241T during fermentation. The genome of L. suionicum DSM 20241T consists of a circular chromosome (2026.8 Kb) and a circular plasmid (21.9 Kb) with 37.58% G + C content, encoding 997 proteins, 12 rRNAs, and 72 tRNAs. Analysis of the metabolic pathways of L. suionicum D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This is the main reason why there is lower (p < 0.05) acetic acid content and higher (p < 0.05) lactic acid content in nLP silage than in other silages. Leuconostoc performs heterolactic acid fermentation and can metabolize diverse organic compounds to produce acetic acid [45]. Compared with control, inoculations of functional LAB (LB, nLP, and pLP) increased the relative abundance of Lactiplantibacillus by 21.62-75.88% but decreased that of Leuconotoc by 16.88-75.05% in silages.…”
Section: Resultsmentioning
confidence: 99%
“…This is the main reason why there is lower (p < 0.05) acetic acid content and higher (p < 0.05) lactic acid content in nLP silage than in other silages. Leuconostoc performs heterolactic acid fermentation and can metabolize diverse organic compounds to produce acetic acid [45]. Compared with control, inoculations of functional LAB (LB, nLP, and pLP) increased the relative abundance of Lactiplantibacillus by 21.62-75.88% but decreased that of Leuconotoc by 16.88-75.05% in silages.…”
Section: Resultsmentioning
confidence: 99%
“…The ODFM database currently contains 131 complete/draft bacterial genome sequences covering 38 genera with 96 (sub)species, of which 24 (sub)species belong to the genus Lactobacillus 10 , 12 to the genus Leuconostoc 11 16 , seven to the genus Acetobacter 17 , six to the genus Staphylococcus 18 , five to the genus Enterococcus , four (sub)species to each of the genera Pediococcus and Weissella 19 , 20 , three to the genus Lactococcus , two (sub)species to each of the genera Brachybacterium , Clostridium , Corynebacterium , and Pseudomonas , and one species to each of the genera Alishewanella 21 , Bacillus 22 , 23 , Brevibacterium , Dietzia , Escherichia , Glutamicibacter , Hafnia , Halomonas , Lentibacillus , Listeria , Megasphaera , Microbacterium , Morganella , Mycetocola , Oceanobacillus , Paracoccus , Pectinatus , Pistricoccus , Propionibacterium , Salimicrobium 24 , Streptococcus , Tetragenococcus , and Vibrio . As for archaea, 38 complete/draft genome sequences of extremely halophilic archaea (19 genera with 36 species) are available, including seven species belonging to the genus Haloarcula 25 , four belonging to the genus Halorubrum 26 , three belonging to each of the genera Haloferax and Natronomonas , two belonging to each of the genera Halapricum 27 , Halobacterium 28 , Halolamina 29 and Haloplanus , and one species belonging to each of the genera Haladaptatus 30 , Halalkalicoccus , Halarchaeum , Halobellus 31 , Halococcus , Halogeometricum , Halopenitus , Halorhabdus , Halostella , Haloterrigena 32 , and Natrinema 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The viral metagenomic sequences have been deposited in the European Bioinformatics Institute (EMBL-EBI) database 35 and are available under accession number PRJEB23957. Details on ODFM database contents are provided in Supplementary Table S1 1 , 7 , 9 14 , 16 34 , 36 108 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, LEfSe results indicated that Leuconostoc was enriched in CK groups, while Weissella was enriched in the LB group. Both primarily perform hetero-fermentation, converting various organic compounds into acetic acid ( Chun et al, 2017 ), contributing to elevated acetic acid levels in CK and LB silage groups.…”
Section: Discussionmentioning
confidence: 99%